Complete response to pembrolizumab for metastatic urothelial carcinoma in the renal pelvis of allograft kidney. Issue 3 (25th March 2022) - Kamei, Jun; Yokoyama, Hirotaka; Niki, Toshiro; Suda, Ryosuke; Sugihara, Toru; Fujisaki, Akira; Ando, Satoshi; Iwami, Daiki; Fujimura, Tetsuya
Abstract : Introduction: We present a case of urothelial carcinoma in a renal allograft successfully treated with pembrolizumab. Case presentation: A 39‐year‐old woman presented with nausea and anorexia 9 years after a renal transplantation. Positron emission tomography revealed a neoplasm of the renal pelvis of the allograft and multiple lymph nodes with peritoneal metastasis. A diagnosis of a non‐muscle‐invasive bladder tumor with peritoneal dissemination and jejunal metastasis of urothelial carcinoma was made. After five cycles of gemcitabine and carboplatin, the tumor progressed and pembrolizumab was administered. One week after the first dose, the allograft was rejected, necessitating arterial embolization. After the second cycle, the patient developed Stevens‐Johnson syndrome. After discontinuing pembrolizumab, positron emission tomography revealed no increased tumor activity. A complete response was achieved for 21 months without additional treatment. Conclusion: Pembrolizumab was effective in treating urothelial carcinoma of the renal allograft; however, allograft rejection and loss should be considered.